Diabetic vitrectomy in a large type 1 diabetes patient population: long‐term incidence and risk factors. (3rd August 2013) - Ostri, Christoffer; la Cour, Morten; Lund‐Andersen, Henrik
Abstract Purpose Diabetic vitrectomy represents an end‐point of diabetic retinopathy progression. This study was designed to estimate long‐term incidence of diabetic vitrectomy and associated risk factors. Methods Retrospective review of prospectively collected data from a large diabetes centre between 1996 and 2010. Surgical history was obtained from The Danish National Patient Register. Results The population consisted of 3980 patients with type 1 diabetes. Median follow‐up was 10.0 years. In total, 106 patients underwent diabetic vitrectomy in the observation period. Surgery indications were nonclearing vitreous haemorrhage (43%) or tractional retinal detachment (57%). The cumulative incidence rates of diabetic vitrectomy were 1.6% after 5 years and 2.9% after 10 years. When excluding patients with no or mild diabetic retinopathy, the corresponding rates were higher; 3.7% and 6.4%, respectively (p < 0.001, log‐rank test). The risk of reaching diabetic vitrectomy increased in patients experiencing glycosylated haemoglobin A1c > 75 mmol/mol in the observation period (p < 0.001, hazard ratio: 3.9, Cox regression analysis). Systolic blood pressure ≥ 140 mmHg, diastolic blood pressure ≥ 90 mmHg, diabetes duration, age, gender and nephropathy were not associated with an increased risk of reaching diabetic vitrectomy (p > 0.05 for all variables). Conclusions Diabetic vitrectomy is rarely required in a type 1 diabetes population with varying degrees of retinopathy, but the risk increases markedly with poor metabolic control.